The Chair's Summing Up Independent Evaluation Office : IMF advice on Capital Flows Executive Board Meeting 20/93 September 18, 2020. (Policy Papers; Policy Paper, 2020)
Executive Directors welcomed the report of the Independent Evaluation Office (IEO) on IMF Advice on Capital Flows. Directors appreciated the high quality of the report, and its thematic and background country studies. Directors welcomed the finding that the adoption of the Institutional View (IV), along with the development of other frameworks and additional tools, had represented a major advance in the Fund's policy framework to provide systematic advice to member countries on the management of capital flows and capital account liberalization. Directors also noted the conclusion that, in its application, the Fund had generally followed the IV and other policy frameworks to ensure that the advice was consistent, tailored to country circumstances, and evenhanded across countries. Directors welcomed that capital flow management measures (CFMs) have generally not been used to substitute for warranted policy adjustments. Directors also welcomed the finding that most authorities broadly support the IV's sequenced framework to capital account liberalization and appreciated the Fund's specific advice in many cases, especially in the context of technical assistance. More recently, faced with the abrupt capital flow reversals during the COVID-19 crisis, Directors noted that emerging markets and developing economies generally followed a multi-pronged approach broadly consistent with the IV framework and made relatively little use of CFMs.